Making the impossible possible : My work for leprosy elimination and human rights - Sasakawa, Yohei (Hurst & Company, 2023)
Making the Impossible Possible chronicles his mission of advocacy and commitment to eliminating leprosy and fostering measures to protect the rights of those living with the disease, many of whom suffer in solitude, forced to exist on the edges of society. Although there has been significant progress in the battle against both disease and the stigma it has long carried, the "last mile" of the journey remains the hardest part. Recording over 200 trips to nearly 70 countries since 2001, Sasakawa has visited far-flung villages to see the plight of the people firsthand and seek local solutions.